Safety, Tolerability, and Pharmacokinetics of NIM‐1324 an Oral LANCL2 Agonist in a Randomized, Double‐Blind, Placebo‐Controlled Phase I Clinical Trial - Andrew Leber; Raquel Hontecillas; Nuria Tubau‐Juni; Josep Bassaganya‐Riera (Clinical and Translational Science)
ABSTRACT NIM‐1324 is an oral investigational new drug for autoimmune disease that targets the Lanthionine Synthetase C‐like 2 (LANCL2) pathway. Through activation of LANCL2, NIM‐1324 modulates CD4+ T cells to bias signaling and cellular metabolism toward increased immunoregulatory function while providing similar support to phagocytes. In primary human immune cells, NIM‐1324 reduces type I interferon and inflammatory cytokine (IL‐6, IL‐8) production. Oral NIM‐1324 was assessed for safety, tolerability and PK in normal healthy volunteers in a randomized, double‐blind, placebo‐controlled trial. Subjects (n = 57) were randomized into five single ascending dose (SAD) cohorts (250, 500, 750, 1000, 1500 mg, p.o.) and three multiple ascending dose (MAD) cohorts (250, 750, 1500 mg QD for 7 days, p.o.). NIM‐1324 did not increase total AE rates in individual cohorts or pooled active groups in SAD or MAD with no SAEs in the study. Oral NIM‐1324 dosing does not result in any clinically significant findings by biochemistry, coagulation, ECG, hematology, or urinalysis when compared to placebo. Plasma exposure, as measured by area under the curve from 0 to 24 h (AUC0‐24), scaled dose proportionally over 250–1000 mg. At 250 mg, NIM‐1324 successfully engaged the target with an upregulation of Lancl2 and key transcriptional biomarkers in whole blood. In conclusion, NIM‐1324 treatment is well‐tolerated up to daily oral doses of at least 1500 mg (nominal), a ≥ six‐fold margin over the anticipated therapeutic dose, and 1000 mg (maximum observed exposure), at least a four‐fold margin over the anticipated therapeutic dose with no dose limiting toxicities.